2012
DOI: 10.1002/hed.23114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intradermal human recombinant copper‐zinc superoxide dismutase on random pattern flaps in rats

Abstract: The beneficial effect of HR-CuZnSOD on flap survival is attained when it is given intradermally into the flap tissue. Theoretically, Hr-CuZnSOD delivered with local anesthetics used in flap elevation may be a valuable clinical tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…In a murine model study, Ophir Schein reported increased ischemic flap viability using Cu-Zn SOD in intradermal injections 15 minutes before incisions at a dose of 50mg/kg. The group received intradermal Cu-Zn SOD presented viability in 49.18mm while control group in 34.84mm (p> 0.01) (38).…”
Section: Reactive Oxygen Species (Ros) Scavengersmentioning
confidence: 84%
“…In a murine model study, Ophir Schein reported increased ischemic flap viability using Cu-Zn SOD in intradermal injections 15 minutes before incisions at a dose of 50mg/kg. The group received intradermal Cu-Zn SOD presented viability in 49.18mm while control group in 34.84mm (p> 0.01) (38).…”
Section: Reactive Oxygen Species (Ros) Scavengersmentioning
confidence: 84%
“…Surgical procedures such as surgical delay, ischemic preconditioning, and flap prefabrication, as well as pharmacological agents such as sympatholytics, vasodilators, calcium channel blockers, anticoagulants, free radical scavenging antioxidants, and growth factors (bFGF, PDGF, TGF, VEGF), can be used for this purpose. (4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques have been described to overcome necrosis, often requiring secondary surgical intervention. Various surgical procedures, including surgical delay, ischemic preconditioning, and flap prefabrication, as well as pharmacological agents like sympatholytic, vasodilators, calcium channel blockers, anticoagulants, free radical scavenging antioxidants, and growth factors (such as bFGF, PDGF, TGF, and VEGF), can be used for this purpose (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Flep kayıplarını ortadan kaldırmak ve azaltmak için çok sayıda teknik tanımlanmıştır. İki basamaklı bir işlem olan cerrahi geciktirme (delay fenomeni), iskemik ön koşullandırma, vasküler implantasyon ile flep prefabrikasyonu kullanılabilmekle beraber pratik uygulamada daha çok sempatolitik, vazodilatör, kalsiyum kanal blokörü, antikoagülan, serbest radikal temizleyici antioksidan ilaçlar ve büyüme faktörleri (bFGF, PDGF, TGF ve VEGF) kan akımının artırılması ve neovaskülarizasyonun sağlanması için kullanılmıştır (2)(3)(4)(5)(6)(7)(8). Kullanılan diğer bir alternatif de tam kandan elde edilen trombositten zengin ürünlerdir (1,(8)(9)(10).…”
Section: Introductionunclassified